Study of Electrical Energy Saving Opportunities Faculty Of Economy And Business Tanjungpura University - Hasma, Muhammad Fathurrahman; Abidin, Zainal; Junaidi, Junaidi (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
The energy audit at the Faculty of Economics and Business, Tanjungpura University has a goal to save energy use and achieve efficient use of electrical energy without affecting the system function and usability of a system. This energy audit uses a detailed energy audit method conducted for lighting systems and air conditioning systems. The research results from the Energy Saving Opportunities (PHE) carried out have 3 stages, namely No Cost, Low Cost and High Cost. At the High Cost PHE by replacing lower lamp power, replacing AC units with lower power consumption. The initial IKE value before PHE was 100.039 kWh/ /year, after   PHE High Cost the IKE value was 95,213 kWh/ /year. The savings generated after doing PHE High Cost is Rp.34,644,672.